The ASEAN experience : insights for regional political cooperation (South Centre GenevaCH, 2007)
Provides a background on the history of ASEAN regional political cooperation and the insights it can provide to developing countries seeking to build greater integration in their region. Focuses on security, energy, the environment, health issues and cross-border movements of people.
Keywords: ASEAN